1992
DOI: 10.1038/360186a0
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone binding to two rodent urinary proteins revealed by X-ray crystallography

Abstract: The principal protein excreted in male rat urine, urinary alpha 2-globulin and the homologous mouse protein, major urinary protein, have been well characterized, although their functions remain unclear. Male rat urine affects the behaviour and sexual response of female rats, leading to the proposal that rodent urinary proteins are responsible for binding pheromones and their subsequent release from drying urine. Urinary alpha 2-globulin is also involved in hyaline droplet nephropathy, an important toxicologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
284
4
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(301 citation statements)
references
References 21 publications
12
284
4
1
Order By: Relevance
“…standing of how the family has evolved, suggesting that it is very much older and more widespread than has been supposed. In contrast with their low conservation at the sequence level, analysis of available lipocalin crystal structures, which include plasma retinol-binding protein (RBP) [11], β-lactoglobulin (Blg) [12], insecticyanin [13], bilin-binding protein (BBP) [14,15], major urinary protein (MUP) and α #u -globulin [16], odorant-binding protein (OBP) [17] and epididymal retinoic acid-binding protein [18], shows that the overall folding pattern common to the lipocalins is highly conserved. The nature of this common structure is now well described (see Figures 1 and 2) [2,11].…”
Section: Subunit Molecularmentioning
confidence: 99%
See 1 more Smart Citation
“…standing of how the family has evolved, suggesting that it is very much older and more widespread than has been supposed. In contrast with their low conservation at the sequence level, analysis of available lipocalin crystal structures, which include plasma retinol-binding protein (RBP) [11], β-lactoglobulin (Blg) [12], insecticyanin [13], bilin-binding protein (BBP) [14,15], major urinary protein (MUP) and α #u -globulin [16], odorant-binding protein (OBP) [17] and epididymal retinoic acid-binding protein [18], shows that the overall folding pattern common to the lipocalins is highly conserved. The nature of this common structure is now well described (see Figures 1 and 2) [2,11].…”
Section: Subunit Molecularmentioning
confidence: 99%
“…There is increasing evidence, from a wide variety of different tissues, that RBP binding to its target cells occurs via specific surface receptors [27,28]. A cell-surface receptor for α " -microglobulin (A1M) has also been identified [29,30], and there is additional evidence to suggest the existence of receptors for MUP [16], Blg [12,31], and OBP [32]. Epidydimal secretory protein has been shown to bind to the plasma membrane of spermatozoa [33], and may be another lipocalin to act via a specific surface receptor.…”
Section: Receptor Bindingmentioning
confidence: 99%
“…Likewise, retinoids are required for processes such as vision, reproduction, and hematopoiesis. Furthermore, due to a powerful growth inhibitory effect on a (Bocskei et al, 1992), lepa-A (Newcomer, 1993), and lbbp-D (Huber et al, 1987). Extended regions and the helix were presented in different colors: El, green; E2, brown; E3-4, cyan, E5, blue; E6-7, red; E8, magenta; H1, yellow.…”
Section: Discussionmentioning
confidence: 99%
“…20 Interestingly, SBT binds to MUP-IV about 20 times more tightly than to any of the five most abundant group 1 isoforms. 20 The first X-ray crystal structure of MUP 21 confirmed that the mouse MUP belong to the lipocalin superfamily. 22 X-ray and NMR structures of MUP-I and MUP-II have been determined in the presence of SBT 23,24 as well as other ligands.…”
Section: Introductionmentioning
confidence: 93%
“…This is consistent with the findings of other groups, where significant difference electron density peaks are observed in the MUP binding pocket even in the absence of exogenously introduced ligand. 21,24,26 Data collection and refinement statistics are presented in Table I.…”
Section: Ligand-protein Interactions In Mup-ivmentioning
confidence: 99%